Metode Pembelajaran Problem Besed Learning Dalam Upaya Meningkatkan Pencapaian Pembelajaran Mata Kuliah Keperawatan Medikal Bedah III Pada Mahasiswa Semester IV Jurusan Keperawatan Politeknik Kesehatan Surakarta - Dwi Susi Haryati; Yeni Tutu Rohimah (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Methods of Learning, Problem Based Learning, Learning Achievement. This study aims to assess the Problem Based Learning in improving the achievement of learning outcomes in the Course of Medical-Surgical Nursing III on IV semester student of Polytechnic nursing Surakarta. The method used in this research was experimental research with quasi-experimental design (posttest control group designs). The mean value of the pre-test knowledge of the discussion group 54 ± 9.65. The mean value of post-test discussion group 74.16 ± 4.46, p = 0.000 a significant improvement. The mean value of pre-test PBL group 54.1 ± 8.25, the mean value of post-test knowledge PBL group 74.00 ± 4.4, p = 0.000 a significant improvement. The mean value of Psychomotor (skills) in a discussion group 92.5 ± 6.08, the mean value of 92.92 ± PBL group skills 6,24. Rerata value attitudes discussion group 87.0 ± 3.43, the mean value of the attitude of PBL group 86.7 ± 3.42. Problem Based Learning method can improve the achievements of Course Study abroad in Medical-Surgical Nursing III on IV semester student of Polytechnic nursing Surakarta.